1994
DOI: 10.1111/j.1365-2141.1994.tb05126.x
|View full text |Cite
|
Sign up to set email alerts
|

The development of antiphospholipid antibodies in haemophilia is linked to infection with hepatitis C

Abstract: In haemophilia the presence of antibodies to antiphospholipid has been linked with HIV infection, but other possibilities have not been fully explored and the specificity for various phospholipids not established. In order to investigate further the pathogenesis and clinical significance of these antibodies, we have determined IgG and IgM antibodies to a variety of phospholipids, including cardiolipin, in the serum of 52 haemophiliacs, and related our findings to the presence of antibodies to HIV and hepatitis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
1
1

Year Published

1995
1995
2005
2005

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(30 citation statements)
references
References 10 publications
3
25
1
1
Order By: Relevance
“…These conclusions are further supported by the findings of a very low prevalence of patients who tested positive in 3 tests for aPL antibodies. The latter finding contrasts with other reports in which the prevalence of positive anti-cardiolipin in hemophiliacs was high and associated with the occurrence of such markers of infections as HIV (4 ), HCV (20 ), or both (20 ). The low prevalence of HIV (8 of 49 patients) in our cohort may in part explain the contrasting findings.…”
Section: Technical Briefscontrasting
confidence: 56%
“…These conclusions are further supported by the findings of a very low prevalence of patients who tested positive in 3 tests for aPL antibodies. The latter finding contrasts with other reports in which the prevalence of positive anti-cardiolipin in hemophiliacs was high and associated with the occurrence of such markers of infections as HIV (4 ), HCV (20 ), or both (20 ). The low prevalence of HIV (8 of 49 patients) in our cohort may in part explain the contrasting findings.…”
Section: Technical Briefscontrasting
confidence: 56%
“…The non-organ-specific antibodies include the antinuclear, smooth muscle, antineutrophil, and liverkidney microsomal antibodies [11,12,20••,26]. aCL antibodies have also been reported in patients with HCV [11,13•,20••,27-29,30•,,3132•, [33][34][35][36][37][38][39].…”
Section: Table 1 Major Risk Factors For Thrombosismentioning
confidence: 98%
“…6,7 It has been suggested that chronic infection with HCV induces autoimmune reactions to platelets, leading to thrombocytopenia. 8,9 Recently, an association between HCV infection and anticardiolipin antibodies was suggested, 10 and anticardiolipin antibodies have been implicated in HCV-associated thrombocytopenia. 11 Antiphospholipid antibodies, which include anticardiolipin antibodies, are a family of autoantibodies against negatively charged phospholipids that are complexed with phospholipid-binding proteins.…”
Section: Introductionmentioning
confidence: 99%